2018
DOI: 10.1016/j.jvs.2017.06.103
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of thoracic endovascular aortic repair in adult coarctation patients

Abstract: Adult AC patients can be treated safely with TEVAR, and the annular constriction of an AC can be successfully dilated by the stent graft. Given these findings, a greater number of patients with longer term follow-up is warranted to further define the role of TEVAR in the management of adult AC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…With the use of the covered stent, an extremely less rate of recoarctation and low incidence of pseudoaneurysm are reported. 1,6) The fabric within the stent provides additional structural support, creates a protective barrier at the site of stent placement, and reduces the risk of vascular trauma. 6) However, because of the required size of the access route and compliance to the growth of body, their use in small children is limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the use of the covered stent, an extremely less rate of recoarctation and low incidence of pseudoaneurysm are reported. 1,6) The fabric within the stent provides additional structural support, creates a protective barrier at the site of stent placement, and reduces the risk of vascular trauma. 6) However, because of the required size of the access route and compliance to the growth of body, their use in small children is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The size selection of the device may be controversial. 6) In our case, the size of the covered stent was selected according to the diameter of the proximal and distal landing zone, similarly to the treatment for aneurysm. To expand the coarctation, a smaller size than the present case would be sufficient and decrease the risk of aortic rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lala et al reported 21 adult patients with primary coarctation or post repair complications, four of whom had pseudoaneurysm and were treated with TEVAR, with acceptable results and no mortality. However, there were cases with reported endoleaks and patients requiring reinterventions during their 8 months of follow-up [7]. Erben et al also reported 11 patients with postoperative aneurysm/pseudoaneurysm in their case series, all of whom were treated with stent grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic endovascular aortic repair is an accepted alternative to open surgical repair for this complicated problem because of lower perioperative morbidity and mortality and quicker return to baseline function compared with open repair 3 . Review of recent literature shows that adults with a new diagnosis of aortic coarctation can be primarily treated with thoracic endovascular aortic repair 4 . Mohan et al 5 have described a technique of endovascular stent grafting of subclavian artery aneurysm.…”
Section: Discussionmentioning
confidence: 99%